Humic Compound Application Against Soil Quality Improvement and Enhancement of Pepper Plant Growth - Erin Puspita Rini; Sugiyanta Sugiyanta (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2022)
[HUMIC COMPOUND APPLICATION FOR SOIL QUALITY IMPROVEMENT AND ENHANCEMENT OF PEPPER GROWTH]. Pepper (Capsicum Annum) is a strategic commodity that contributes to Indonesia's economy. The price of pepper fluctuates due to the instability of pepper production, which is influenced by multiple factors such as decreasing of soil fertility. Soil conditioner can help to improve soil fertility. The purpose of this research was to determine the effect of humic compounds application on pepper cultivation to improve soil fertility and increase the growth and yield of pepper. The research was conducted from February to August 2021 at the IPB Pasir Sarongge Experimental Field in Cianjur, West Java. The study was conducted using a Completely Randomized Group Design (CRGD) with one factor, humic compound solution concentrations of 0, 2.5, 5, 7.5, 10, and 12.5 mL/L, with each level repeated four times. Duncan's Multiple Range Test (DMRT) was used to separate the mean of the data after variance analysis. The result showed that humic compound application can improve soil fertility, growth and yield of pepper plants as indicated by increasing the value of Cation Exchange Capacity (CEC), decreasing potassium leaching rate and increasing all growth and yield characters except the yield per plant character. The application of 12.5 mL/L humic compounds increased CEC, decreased potassium leaching rate to 0%, increased plant height (37.40%), number of branches (56.72%) and number of fruits (57.81%). The application of humic compounds at 10 mL/L   increases the weight of 10 fruits (30.78%), yield per plant (27.56%), yield per plot and predicted yield per hectare (47.58%).